What Is An Ideal Critical Thinker Expected to Conclude about Anthropogenic Global Warming? - Brambatti Guzzo, Guilherme; Dall'Alba, Gabriel (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2017)
Critical thinking involves the ability to properly assess statements and actions, and it also requires a permanent disposition to appropriately use cognitive skills in the evaluation of any claim. In the present paper, we discuss the characteristics of an ideal critical thinker, and apply them to a contemporary problem, namely anthropogenic global warming (AGW, a hypothesis that accounts for the increase of the average temperature of Earth as a consequence of human activities), in order to discuss what an ideal critical thinker is expected to conclude about the occurrence of this phenomenon. We assume that an ideal critical thinker is able to find out where the most reliable information regarding a certain issue is, is competent to reasonably evaluate it, and has an inclination to calibrate her beliefs according to the results of the inquiry. We thus conclude that an ideal critical thinker is expected to accept the current scientific consensus that AGW is occurring, albeit considering this issue, as well as virtually any other idea, open to revision. The fact that in many occasions people are selective in using critical thinking skills, such as when they reject the massive evidence of AGW, should be a cause of concern for educators, who should motivate their students to think critically about any problem and question they encounter; this, in turn, could help the students to develop a better understanding of the world, take more reasonable courses of action, and be protected against misinformation.